Assessing the effects of earlier snow melt-out on alpine shrub growth: The sooner the better?. (August 2020) - Francon, L.; Corona, C.; Till-Bottraud, I.; Choler, P.; Carlson, B.Z.; Charrier, G.; Améglio, T.; Morin, S.; Eckert, N.; Roussel, E.; Lopez-Saez, J.; Stoffel, M.
Highlights: Shrubs growth rings are relevant indicators of the response of alpine ecosystem to global warming. At the high-elevation site, our results demonstrate a negative effect of snow cover duration. At lower elevations, late frost exposure is shown to lead to growth reduction. Global warming induced a divergence in the growth response of a dominant shrub species to climate. Abstract: Enhanced shrub growth in a warming alpine climate has potential far-reaching implications, including soil nutrient cycling, carbon storage, or water and surface energy exchanges. Growth ring analysis can yield mid- to long-term, annually resolved records of shrub growth, and thereby offer valuable insights into how growth is driven by interannual climate variability. In the European Alps, dendroecological approaches have shown that dwarf shrub productivity is influenced by interannual variations of growing season temperature but results also point to a negative effect of winter precipitation on radial growth. However, as past work lacked snow cover data, links between snow cover duration, growing season length, energy availability and inter-annual shrub growth remain poorly understood. In this paper, we combined multi-decadal shrub-ring series from 49 individuals sampled at three sites along a 600-m elevational gradient in the Taillefer massif, located in the French Alps to assess growth sensitivity of long-lived and widespread Rhododendron ferrugineum shrubs to both snow cover dynamics and temperature changes. To this end, we computed structural equation models to track the response of shrub radial growth to extending growing season at 1800, 2000 and 2400 m above sea level and for two time periods (i.e. 1959–1988 and 1989–2016). The second period is marked by a significant advance in snow melt-out resulting in a regime shift highlighted at the end of the 1980s by a breakpoint analysis. At the high-elevation site, our results demonstrate a positive effect of increasing growing season length on shrub growth, which is strongly dependent on snowpack depth and snow cover duration. Conversely, at lower elevations, earlier melt-out dates and associated late frost exposure are shown to lead to radial growth reduction. Moreover, the climate signal in ring-width chronologies of R. ferrugineum portrays a weakening since 1988 – similar to a phenomenon observed in series from circumpolar and alpine tree-ring sites and referred to as "divergence". By analyzing long-term records of radial growth along an elevation gradient, our work provides novel insights into the complex responses of shrub growth to climate change in alpine environments. This paper demonstrates that R. ferrugineum, as a dominant alpine shrub species, behave as an ecological indicator of the response of alpine ecosystem to global warming.